2019
DOI: 10.1080/15476278.2019.1644889
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of HIF-1α and HIF-2α in tissue regeneration: a study of hypoxia in house gecko tail regeneration

Abstract: The house gecko (Hemidactylus platyurus) has evolved the ability to autotomize its tail when threatened. The lost part is then regrown via epimorphic regeneration in a process that requires high energy and oxygen levels. Oxygen demand is therefore likely to outstrip supply and this can result in relative hypoxia in the tissues of the regenerating tail. The hypoxic state is stabilized by the Hypoxia Inducible Factor-1α (HIF-1α) and HIF-2α proteins. We induced tail autotomy in 30 mal H. platyurus Correspondence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Specifically, the early blastema during newt and axolotl limb regeneration is avascular (Mescher, 1996;Peadon and Singer, 1966), while neovascularization in axolotl occurs later in blastema formation and relies on VEGF signaling (Ritenour and Dickie, 2017). Using qPCR at different time points of the regenerating gecko tail, it was shown that HIF1α mRNA is upregulated early, highlighting the initial hypoxic state during blastema formation (Novianti et al, 2019). Additionally, slice cultures of the regenerating mouse digit-tip blastema revealed that dynamic changes in oxygen may contribute to bone regenerationnamely, that initial hypoxic events in the blastema followed by increasing oxygen concentrations from vascularization may promote bone mineralization (Sammarco et al, 2014).…”
Section: Metabolic Cues and Heterogeneitymentioning
confidence: 99%
“…Specifically, the early blastema during newt and axolotl limb regeneration is avascular (Mescher, 1996;Peadon and Singer, 1966), while neovascularization in axolotl occurs later in blastema formation and relies on VEGF signaling (Ritenour and Dickie, 2017). Using qPCR at different time points of the regenerating gecko tail, it was shown that HIF1α mRNA is upregulated early, highlighting the initial hypoxic state during blastema formation (Novianti et al, 2019). Additionally, slice cultures of the regenerating mouse digit-tip blastema revealed that dynamic changes in oxygen may contribute to bone regenerationnamely, that initial hypoxic events in the blastema followed by increasing oxygen concentrations from vascularization may promote bone mineralization (Sammarco et al, 2014).…”
Section: Metabolic Cues and Heterogeneitymentioning
confidence: 99%
“…There is an interesting link between apoptosis and reactive oxygen species (ROS). ROS are detected early in regeneration and are necessary for regeneration in multiple species ( Love et al, 2013 ; Ferreira et al, 2018 ; Novianti et al, 2019 ). Perhaps not coincidentally, ROS are important for apoptosis-dependent regeneration.…”
Section: Initiation and Regulation Of Regenerative Apoptosismentioning
confidence: 99%
“…Geckos (family Gekkonidae) have skin characteristics that look soft even though they remain scaly, are active at night (nocturnal) and can sever the tip of their tail (autotomy) as a form of self-defense and avoid predators (Barton, 2007;Leo et al, 2020;Novianti et al, 2019;Rakhmiyati and Jaâ, 2018) Cosymbotus platyurus is a species of common house gecko that is commonly found in Indonesia. This species has a wide range of distribution including India, Southeast Asia, to Australia.…”
Section: Introductionmentioning
confidence: 99%